Василий Васильевич Докучаев (1846-1903) - Чеботарева Л. А. (Материалы к биобиблиографии ученых СССР, 1947)
Экземпляры: КХ (20060322) / Инвентарный номер: 96683 / Сис.шифр: 91.9:4 / Авт.знак: Ч-34 / ГРНТИ: 68 / ББК: 91.9:4